Biogeography of Southern Ocean Active Prokaryotic Communities Over a Large Spatial Scale - Maturana-Martínez, Claudia; Iriarte, José Luis; Ha, Sun-Yong; Lee, Boyeon; Ahn, In-Young; Vernet, Maria; Cape, Mattias; Fernández, Camila; González, Humberto E.; Galand, Pierre E. (Frontiers in Microbiology, 2022)
The activity of marine microorganisms depends on community composition, yet, in some oceans, less is known about the environmental and ecological processes that structure their distribution. The objective of this study was to test the effect of geographical distance and environmental parameters on prokaryotic community structure in the Southern Ocean (SO). We described the total (16S rRNA gene) and the active fraction (16S rRNA-based) of surface microbial communities over a 6,500 km longitudinal transect in the SO. We found that the community composition of the total fraction was different from the active fraction across the zones investigated. In addition, higher α-diversity and stronger species turnover were displayed in the active community compared to the total community. Oceanospirillales, Alteromonadales, Rhodobacterales, and Flavobacteriales dominated the composition of the bacterioplankton communities; however, there were marked differences at the order level. Temperature, salinity, silicic acid, particulate organic nitrogen, and particulate organic carbon correlated with the composition of bacterioplankton communities. A strong distance–decay pattern between closer and distant communities was observed. We hypothesize that it was related to the different oceanic fronts present in the Antarctic Circumpolar Current. Our findings contribute to a better understanding of the complex arrangement that shapes the structure of bacterioplankton communities in the SO.